Testing the impact of external sovereign debt on Turkey’s ecological footprint: New evidence from the bootstrap ARDL approach - Xu, Wenyun; Jahanger, Atif; Inuwa, Nasiru; Samour, Ahmed; Ibrahim, Saifullahi Sani (Frontiers in Environmental Science, 2022)
As is glaringly apparent, the world is now bedeviled with environmental challenges and ecological complications. This may not be unconnected with the persistent ecological challenges emanating from fossil fuel consumption and changing lifestyles. This is why various attempts are ongoing to advance the course of renewable energy and economic growth as a response to environmental change. Therefore, this study seeks to investigate the dynamic effect of external debt, energy usage, and real income on the ecological footprint in Turkey, covering the period 1985–2017. To achieve the stated objective, the study used the newly developed Bootstrap Autoregressive Distributed Lag (BARDL) test and the Granger causality test to unravel the co-movement as well as the direction of causality among the variables. The results revealed that external debt influences environmental quality in both the short and the long run. However, energy consumption and real income have been found to have retarded environmental quality in both the short and the long run. The Granger causality test results revealed that the causal flow direction runs from external debt, economic growth, and energy usage to environmental quality. Therefore, the study argues that for the Turkish government to achieve a long-term plan of environmental sustainability, there is a need for the government to venture into debt consolidation programs such as implementing tax increases and cutting public spending in order to increase fiscal space that would finance long-term environmental protection policies.